Utilization of Smart Cards in Integer Operations Material to Improve Junior High School Students' Understanding - Ahsan, Jauhari Fadil; Avita, Dwi; Sumaji (International Journal of Elementary Education, 2024)
The problem currently occurring is that there are still many students who consider mathematics to be a complicated science because mathematics is abstract. This has an impact on student interest in learning and low learning outcomes. Therefore, this research aims to analyze the effect of using learning in the form of smart cards in increasing students' understanding of integer operations. This type of research is quantitative research using quasi-experimental methods. The research design was a pre-experimental experimental design with a one-group pretest post-test design. The research subjects were junior high school students with 21 students. The methods used to collect data are observation and tests. The instrument used to analyze data is a test question sheet. The technique used to analyze data is inferential statistics. The data analysis technique in this research uses the t-test and hypothesis testing. This research found that the average student score increased after implementing smart card media in the learning process. In contrast, at the pretest, students only got an average score of 50.24, and after implementing smart card media, the average student score on the post-test was 72.62. This research also found a significant influence between the use of smart card media and students' understanding of integer operations. It was concluded that smart card media can improve junior high school students' understanding of integer operations.